Carl Schmitt's European Jurisprudence - Bogdandy, Armin von 1960- HerausgeberIn; Mehring, Reinhard 1959- HerausgeberIn; Hussain, Adeel HerausgeberIn (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2022)
With the publication of the pamphlet The Situation of European Jurisprudence, Schmitt reinvented himself as an author after 1945 and prepared the ground for his work The Nomos of the Earth, which appeared a few months later. The following book offers a productive approach to this hermeneutically demanding and strategic text by providing a translation of the 1950 version and commenting on its historical and philological context. This book then offers plural confrontations, adaptations, and transformations that Schmitt's text implies for European jurisprudence today. It thus departs from the usual form of a commentary by clearly separating explication and transformation and proposes to employ an actualisation for the twenty-first century. With contributions by Oren Gross, Adeel Hussain, Reinhard Mehring, Michael Stolleis, Christian Tomuschat and Armin von Bogdandy